Influência da altura do abutment angulado na distribuição das tensões em implantes de hexágono externo com próteses unitárias implantossuportadas - Lara, Leonardo Augusto Santana [UNESP] (2010)
The aim of this study was to evaluate the influence of the height of angled abutments for single implant-supported prostheses with external hexagonal implant, by means of photoelasticity. It was confectioned two models in photoelastic PL-2, each model consists of a block with one external hexagon implant of 4.0x10mm (Conexão Sistema de Prótese, Ltda., São Paulo, Brazil). Model 1 - Implant prosthesis screwed UCLA angled at 17°, Model 2 - Implant prosthesis screwed UCLA at 30°, model 3 - Implant prosthesis screwed and abutment estheticone at 17 °with 2mm height, model 4 - Implant prosthesis screwed and abutment estheticone at 30° with 3mm height, Model 5 - Implant prosthesis screwed and abutment estheticone at 17° with 3mm height, model 6 - Implant prosthesis screwed and abutment estheticone at 30° with 4mm height. The prostheses were fabricated with standard heights and NiCr alloy. For visualization of photoelastic fringes, was used a circular polariscope and were applied axial and oblique 100 N load by the universal testing machine. The results were photographed and analyzed qualitatively using Adobe Photoshop software. In axial loading, the models showed photoelastic fringes of low intensity in the apical and cervical area is that of stress concentration increased as they increased the height of the abutment. In oblique loading, there were a greater number of fringes on the opposite side of the slope of the crown. The fringes were more forthcoming as abutment angulation increased. It was concluded that: the abutment UCLA showed a more favorable stress distribution; with the increased of the height abutment, increased stress. With increase implant angulation, showed the greatest stress concentration